(untitled) (Journal of Mathematics Mechanics and Computer Science, 2022)
Due to the lack of domestic manufacturers, the production of a microreactor with a control system for chemical processes will remain relevant. The reason for this is the demand for automated solutions and, in general, automation and research into the optimal conditions for promising chemical processes in companies and in production. Moreover, the microreactor proposed with a chemical process control system will be able to save money and time on the development of effective chemical processes for the production of a wide variety of substances. In addition, the project provides for the use of composite and polymer materials for work, which in turn will reduce the cost of manufactured products, and at the same time increase the competitive attractiveness. The aim is to develop a microreactor and a control system for chemical processes. This goal is achieved by justifying the choice of the direction of research, analysis of existing equipment for carrying out microreactor synthesis, application for their creation lightweight, composite and other technical materials, as well as through the development of technology for creating microreactor equipment using 3D printing, milling and engraving of light metals, composite and polymer materials. The article presents microreactors and the development of a microreactor for the production of vinyl acetate, a detailed description of the methodology for the development of this complex device, including a microreactor, a SCARA type robot and a control unit. Methods for the production of vinyl acetate and the possibility of automating this process with a complex device were also studied.